2008
DOI: 10.4314/njgc.v6i1.37085
|View full text |Cite
|
Sign up to set email alerts
|

A Study of The Academic Achievement and Self-Concept of Male and Female Hearing-Impaired Students in Nigeria

Abstract: The main purpose of the study was to examine the academic achievement and self-concept of male and female hearing-impaired students in Nigeria. In doing so, a purposive sampling procedure was employed to elicit responses from 566 (364 males and 204 females) hearing-impaired secondary school students identified in various parts of the country. The Adolescent Personal Data Inventory (APDI) was used to measure self-concept while the respondents' Junior Secondary Certificate Examination (JSCE) results were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…This implied that the male and female students with special educational needs were doing averagely well in their studies. This observation was similar to Akinpelu (1998) who found that there was no significant difference between the academic achievement of male and female hearing‐impaired students. However, this result differed from Babatola (1987) who found that male hearing impaired students performed slightly better than female hearing impaired students.…”
Section: Discussionsupporting
confidence: 89%
“…This implied that the male and female students with special educational needs were doing averagely well in their studies. This observation was similar to Akinpelu (1998) who found that there was no significant difference between the academic achievement of male and female hearing‐impaired students. However, this result differed from Babatola (1987) who found that male hearing impaired students performed slightly better than female hearing impaired students.…”
Section: Discussionsupporting
confidence: 89%
“…Studies indicate that, although hearing-impaired students' have normal cognitive abilities, their academic achievements are lagging far behind than their peers of the same age and academic level (Akinpelu, 1998;Antia, Jones, Reed, & Kreimeyer, 2009;Lang, 2002;Qi & Mitchell, 2012).…”
Section: Resultsmentioning
confidence: 99%